Non-contrast computed tomography in the diagnosis of cerebral venous sinus thrombosis - Avsenik, Jernej (Radiology and oncology (Ljubljana), 2016)
Due to the diversity of underlying factors and the absence of a uniform treatment approach, diagnosis and management of patients with cerebral venous sinus thrombosis (CVST) remain a challenging task.1 CVST represents 0.5% to 1% of all strokes and affects approximately 5 patients per million every year, but has a higher frequency among younger patients. Typical acquired risk factors include recent surgery, trauma, pregnancy, postpartum state, antiphospholipid syndrome, cancer and use of oral contraceptives. Cases of inherited thrombophilia include Antithrombin III, Protein C and Protein S deficiency, factor V Leiden positivity, prothrombin gene mutation and hyperhomocisteinemia. Infection of parameningeal spaces (ears, paranasal sinuses, oral cavity, face and neck) is common cause of CVST in pediatric population but rare in adults. The symptoms of CVST are not specific. The most common complaint is headache which occurs in up to 90% of patients. Additionally, abnormal vision, any of the symptoms of stroke and seizures have been described. In the past D-dimer levels appeared to be of value as an initial screening test. A study in 2004 evaluated the sensitivity of D-dimer to be 97.1% and specificity 99.1%.8 However, later studies showed that up to 10% of patients with CVST have a normal D-dimer. As it is fast, affordable and widely available, non-contrast computed tomography (NCCT) is the most frequently performed imaging study for evaluation of patients with new headache, focal neurological abnormalities, seizure, or change in mental status. A typical imaging finding in patients with CVST is direct visualization of a hyperattenuating thrombus in the occluded sinus (dense sinus sign). Occasionally, NCCT may only show indirect signs of thrombosis, including diffuse brain edema and parenchymal hemorrhage. Sensitivity of NCCT in the diagnosis of CVST was previously considered rather poor. However, using modern multidetector row CT scanners, recent studies report higher sensitivity and specificity values. In addition, Buyck et al. suggest measurement of the venous sinus attenuation to increase the diagnostic yield of the examination. Therefore, the goal of the present study was to evaluate the diagnostic accuracy of NCCT in the diagnosis of CVST in the emergency setting
Keywords: cerebral venous sinus thrombosis; computed tomography; diagnostika; možganski venski sinusi; računalniška tomografija; radiologija; stroke